2020
DOI: 10.1155/2020/8880651
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Rosmarinic Acid on IPEC-J2 Cells Exposed to the Combination of Deoxynivalenol and T-2 Toxin

Abstract: Mycotoxin contamination in feedstuffs is a worldwide problem that causes serious health issues both in humans and animals, and it contributes to serious economic losses. Deoxynivalenol (DON) and T-2 toxin (T-2) are major trichothecene mycotoxins and are known to challenge mainly intestinal barrier functions. Polyphenolic rosmarinic acid (RA) appeared to have antioxidant and anti-inflammatory properties in vitro. The aim of this study was to investigate protective effects of RA against DON and T-2 or combined m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In IPEC-J2 cells, LPS of various origins could not increase H 2 O 2 levels [ 38 ] using Amplex red method which is in good agreement with our present findings. Other mycotoxins such as DON and T2 toxin and their combination could increase EC H 2 O 2 in IPEC-J2 cells, which returned to control levels in the presence of rosmarinic acid [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In IPEC-J2 cells, LPS of various origins could not increase H 2 O 2 levels [ 38 ] using Amplex red method which is in good agreement with our present findings. Other mycotoxins such as DON and T2 toxin and their combination could increase EC H 2 O 2 in IPEC-J2 cells, which returned to control levels in the presence of rosmarinic acid [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that oxidative stress is a crucial factor contributing to DON-caused intestinal toxicity in animals [ 30 ], and the role of oxidative stress induced by DON exposure should be regarded as one of the key mechanisms for its toxicity [ 18 ]. Alleviating oxidative stress would be an effective way to attenuate the toxic effects of DON, thereby reducing its damage to farm animals [ 17 ].…”
Section: Plant-derived Polyphenol Application To Counteract Oxidative...mentioning
confidence: 99%
“…Additionally, the meat quality was improved by dietary supplementation of chlorogenic acid-enriched extract, as suggested by reduced cooking loss, drip loss, carbonyl, and MDA contents in the meat of pigs [ 74 ]. Using an in vitro model of IPEC-J2 cells, Pomothy et al (2020) evaluated the impact of rosmarinic acid on intestinal oxidative stress and inflammation of porcine enterocytes induced by DON and T-2 toxin [ 30 ]. The authors found that a dosage of 50 μmol/L rosmarinic acid restored the decreased transepithelial electrical resistance of IPEC-J2 cell monolayer caused by cotreatment with 1 μmol/L DON + 5 nmol/L T-2 toxin for 48 or 72 h [ 30 ].…”
Section: Plant-derived Polyphenol Application To Counteract Oxidative...mentioning
confidence: 99%
“…In a model using a mixture of the mycotoxins DON and fusariotoxin T 2 (T2) to impair barrier function, rosmarinic acid showed the ability to restore TEER and to promote distribution of TJ protein CLDN-1. Levels of pro-inflammatory IL-6 and IL-8 were further decreased, suggesting an anti-inflammatory potential of rosmarinic acid [ 59 ]. Another study investigated the influence of several PFA on IPEC-J2 cells after deteriorating barrier function by disrupting TJ via a calcium-switch assay.…”
Section: Intestinal Porcine Epithelial Cell Linesmentioning
confidence: 99%
“…Measurement of lactate dehydrogenase (LDH) activity in culture medium further demonstrated the anti-oxidative effect of quercetin as LDH which physiologically is located inside of enterocytes was released into the medium after damage of cellular membrane [ 92 ]. The antioxidative effect of rosmarinic acid was shown in H 2 O 2 -challenged cells [ 91 ] as well as in a mycotoxin-induced stress model [ 59 ].…”
Section: Intestinal Porcine Epithelial Cell Linesmentioning
confidence: 99%